Preface to “A revision of American Trichilia (Meliaceae)” - Pennington, Terence D.; Clarkson, James J. (Phytotaxa, 2016)
Trichilia P.Browne is one of the largest genera of Meliaceae, containing 81 described species in tropical America, 20 species in Africa and 2 species in Madagascar. It is placed in the subfamily Melioideae (Pennington & Styles 1975, Muellner et al. 2003) where it is a well-defined genus with a distinctive floral and fruit structure. It is clearly separated from all other genera of the family by the flowers with a staminal tube of partially or completely fused stamens bearing the anthers at the apex of the filaments or on the margin of the staminal tube and by the fruit which is a 2–3-valved loculicidal capsule containing fleshy seeds partly or completely surrounded by an arillode or rarely a sarcotesta.